Gedsi integration in UMM PGSD student learning tools - Ulum, Bahrul; Amelia, Delora Jantung; Setiono, Panut; Ulum, Ulum; Amelia, Amelia (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
Lack of GEDSI integration can hinder student participation and achievement. Therefore, the integration of GEDSI in learning is the main focus, especially for UMM PGSD students who will become teachers in the future. This research aims to understand the extent to which GEDSI integration occurs in the fifth semester of elementary school social studies learning tools for UMM PGSD students and the obstacles in its integration. The research method uses qualitative descriptive research by analyzing documents in the form of learning tools for PGSD UMM students in the fifth semester (odd) of the 2023/2024 academic year with content analysis techniques, data collection methods through documentation of elementary social studies learning tools that have been prepared by students. In general, 79.9% of students in learning activity content and 98% of students in teaching material texts have integrated GEDSI. In the illustrations and pictures, in the teaching materials section there are 94% of students who have integrated GEDSI and 6% of students have not integrated GEDSI, 53% of students' LKPD have not or have not implemented GEDSI integration and 47% have integrated GEDSI, in the evaluation section there are around 66 .4% of students have integrated GEDSI and 33.6% of students have not or have not integrated GEDSI. Finally, in references or learning resources, there were 0.07% or 1 student who integrated GEDSI and 99.3% had not or did not integrate GEDSI. It is hoped that the results of this research can help create an inclusive and equitable learning environment, as well as produce graduates who are ready to face global challenges.